Are we witnessing the spectre of an HPC meltdown?. (16th October 2018) - Vergara Larrea, Verónica G.; Brim, Michael J.; Joubert, Wayne; Boehm, Swen; Baker, Matthew; Hernandez, Oscar; Oral, Sarp; Simmons, James; Maxwell, Don
Summary: We measure and analyze the performance observed when running applications and benchmarks before and after the Meltdown and Spectre fixes have been applied to the Cray supercomputers and supporting systems at the Oak Ridge Leadership Computing Facility (OLCF). Of particular interest is the effect of these fixes on applications selected from the OLCF portfolio when running at scale. This comprehensive study presents results from experiments run on Titan, Eos, Cumulus, and Percival supercomputers at the OLCF. The results from this study are useful for HPC users running on Cray supercomputers and serve to better understand the impact that these two vulnerabilities have on diverse HPC workloads at scale.